COMMUNITY BASED TOURISM (CBT) SEBAGAI STRATEGI PENGEMBANGAN PARIWISATA BERKELANJUTAN DI DTW CEKING DESA PEKRAMAN TEGALLALANG - Nyoman Surya Wijaya; I Wayan Eka Sudarmawan (Jurnal Ilmiah Hospitality Management, 2019)
Research on Community based tourism as a sustainable tourism development strategy in DTW "Ceking" Pekraman Tegallalang village is done with the aim to study Community Based Tourism (CBT) as a tourism development strategy In DTW Ceking village Pekraman Tegallalang and analyzed the development strategy of CBT in DTW Ceking village Pekraman Tegallalang so that it can be sustainable. Using a research approach with a qualitative and quantitative method (mix method), accompanied by a survey method that will help to get a thorough picture covering physical condition, state of tourism and social situation and Culture at DTW Ceking Village Pekraman Tegallalang. So it is reviewed based on the problem, then research is a description of tourism phenomenon and its relation to socio-cultural life as well as the environment, by taking the research site Yankni DTW Ceking village Pekraman Tegallalang in Kecamatan Tegallalang, Gianyar Regency, Bali Province, Tepatnyareside in the Village Tegallalang, Gianyar. obyekstrainiberbatasandirectly with the Pekramankedisandthe Part of the area Persawahancekingterracurangtepedesapekramankedisan. Data used is qualitative and quantitative data and will be obtained conclusions that are "grounded". The findings of the research with certainty that is the form of Community Based Tourism as a sustainable tourism development strategy in DTW Ceking village Pekraman Tegallalang, Gianyar.